Ã˜Â¯Ã™Ë†Ã˜Â± Ã˜Â§Ã™â€žÃ˜ÂªÃ˜Â±Ã˜Â¨Ã™Å Ã˜Â© Ã˜Â§Ã™â€žÃ˜Â¥Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦Ã™Å Ã˜Â© Ã™ÂÃ™Å Ã˜Â§Ã™â€žÃ˜Â¥Ã™â€ Ã™â€¦Ã˜Â§Ã˜Â¡ Ã˜Â§Ã™â€žÃ˜Â®Ã™â€žÃ™â€šÃ™Å Ã™â€žÃ™â€žÃ˜Â´Ã˜Â¹Ã˜Â¨ (Ã˜Â¯Ã˜Â±Ã˜Â§Ã˜Â³Ã˜Â© Ã˜Â¹Ã™â€žÃ™â€° Ã˜Â§Ã™â€žÃ˜Â¥Ã˜Â³Ã™â€žÃ˜Â§Ã™â€¦ Ã™Ë†Ã˜Â¯Ã™Ë†Ã˜Â±Ã™â€¡ Ã™ÂÃ™Å Ã˜Â§Ã™â€žÃ˜Â¥Ã™â€ Ã™â€¦Ã˜Â§Ã˜Â¡ Ã˜Â§Ã™â€žÃ™â€šÃ™Ë†Ã™â€¦Ã™Å Ã˜Â¨Ã˜Â¥Ã™â€ Ã˜Â¯Ã™Ë†Ã™â€ Ã™Å Ã˜Â³Ã™Å Ã˜Â§) - ZA, Tabrani (UIN Ar-Raniry, 2017)
Islam as a religion of rahmatan li al'alamin, very much its contribution to the national development which is oriented to the whole human development. The presence of religion is always accompanied by